(3cJGH GdSehes - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s ((3Ydi Hf CHj WGdH CMeO Hf eMeO Hf YHO Gdedc GdRjGJ s)
(3ChdgG (B:s
(3bGd CHh HcQ (B: (3gPG GdcJGH LeYJ ajg ef GdcdGe Ydi GdSehe hYdGLGJgG ef cJGH hLOJg s
(3BNQgG (B:s
(3feGQ (B: (3bjd HOdg hQb GdKeGe , HOdg eKdg Khe , hbjd eKdg UfOd s
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B23s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B102 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs